Optimizing Digital Marketing to Increase Awareness, Purchase Intention, and Consumer Retention: A Conceptual Study on MSMEs in Timor Leste - do Ceu Fatima, Arlindo; Soares, Casimiro; das Neves, Cipriano Bruno (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
The development of digital technology has transformed traditional marketing patterns into digital-based strategies that are more interactive, efficient, and broad-reaching. For Micro, Small, and Medium Enterprises (MSMEs) in Timor Leste, the implementation of digital marketing presents a strategic opportunity to increase competitiveness, particularly in building awareness, driving purchase intention, and strengthening consumer retention. This article aims to examine the role of digital marketing optimization in influencing MSME consumer behavior through a review of current literature, relevant theoretical approaches, and primary data collection from MSMEs in Timor Leste. Through in-depth interviews with 15 MSME owners and a survey of 120 MSMEs across Dili, Baucau, and Maliana, this research highlights both the opportunities and challenges in digital marketing adoption. The study reveals the integration of various digital marketing elements, such as social media, content marketing, and e-commerce platforms, which are considered capable of expanding brand exposure, increasing consumer trust, and creating long-term relationships with customers. The primary data findings indicate that while 88% of MSMEs recognize the importance of digital marketing, only 35% actively implement comprehensive digital strategies due to challenges in digital literacy, infrastructure limitations, and resource constraints. Academically, this study contributes to enriching the digital marketing literature in the context of developing countries. Practically, the results of this study are expected to serve as a strategic reference for MSMEs in Timor Leste in optimizing the use of digital technology to expand markets and improve business sustainability.